2019
DOI: 10.1055/s-0039-1693078
|View full text |Cite
|
Sign up to set email alerts
|

Sitting Position in Neurosurgery

Abstract: Neurosurgery in the sitting position is used for resection of tumors located in the cerebellopontine angle, pineal region, other technically difficult tumors in the infratentorial region, as well as surgeries of the cervical spine. Since its inception, the use of this particular position has been contentious due its risk-benefit analysis. With improved microsurgical equipment and surgical and anesthetic techniques, as well as advanced monitoring techniques to assure patient safety, many centers are revisiting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 44 publications
0
4
0
6
Order By: Relevance
“…Pada kraniotomi posisi duduk, selain monitor standar yang digunakan, juga diperlukan monitor tambahan seperti arterial line, central venous catheter (CVC), dan monitor untuk mendeteksi VAE. 6 Seperti pada kebanyakan prosedur kraniotomi, arterial line dipasang pada pasien ini, yang menjadi pertimbangan adalah mengenai posisi transduser untuk arterial line. Pada pasien ini, transduser diletakkan setinggi jantung pasien.…”
Section: Intraoperasi Monitorunclassified
See 2 more Smart Citations
“…Pada kraniotomi posisi duduk, selain monitor standar yang digunakan, juga diperlukan monitor tambahan seperti arterial line, central venous catheter (CVC), dan monitor untuk mendeteksi VAE. 6 Seperti pada kebanyakan prosedur kraniotomi, arterial line dipasang pada pasien ini, yang menjadi pertimbangan adalah mengenai posisi transduser untuk arterial line. Pada pasien ini, transduser diletakkan setinggi jantung pasien.…”
Section: Intraoperasi Monitorunclassified
“…Pemasangan CVC subclavia kanan dilakukan pada pasien ini untuk mengantisipasi terjadinya VAE. 6,8 Monitor tambahan adalah monitor untuk mendeteksi terjadinya VAE. Deteksi VAE dapat dengan menggunakan beberapa modalitas, tidak ada satupun metode yang dapat memprediksi kejadian VAE secara akurat.…”
Section: Intraoperasi Monitorunclassified
See 1 more Smart Citation
“…Goraksha and colleagues, in their review article, describe the potential complications associated with the sitting position in neurosurgical patients. 4 The authors highlight how the collected evidence prove that to ensure patient safety and a successful outcome, a thorough preoperative anesthetic evaluation to decide if the sitting position is suitable for the patient is essential. As in any neurosurgical case, all Neuroanesthesia encompasses clinical management of patients undergoing brain and spine procedures that might require positioning which are not usual in other specialties, and these include the following: prone, lateral (and park bench) and semilateral, as well as sitting and semisitting.…”
mentioning
confidence: 99%
“…The review articles from Boyle et al and Goraksha et al, included in this issue, address appropriate positioning of neurosurgical patients and also provide new and relevant information in this field. 3,4 Boyle and colleagues completed a systematic review that reported evidence relevant for intraoperative positioning in patients undergoing cervical spine surgery with posterior approach. 3 In their review, a total of 9875 studies were retrieved and 20 were selected as appropriate for data analysis.…”
mentioning
confidence: 99%